Prognostic impact of the 2009 UICC/AJCC TNM staging system for renal cell carcinoma with venous extension - Martínez-Salamanca, Juan; Huang, William C.; Millán, Isabel; Bertini, Roberto; Bianco, Fernando J.; Carballido, Joaquin A.; Ciancio, Gaetano; Hernández, Carlos; Herranz, Felipe; Haferkamp, Axel; Hohenfellner, Markus; Hu, Brian; et al. (European urology, 2011)
Background - The prognostic significance of venous involvement and tumour thrombus level in renal cell carcinoma (RCC) remains highly controversial. In 2010, the American Joint Committee on Cancer (AJCC) and the Union International Centre le Cancer (UICC) revised the RCC staging system (7th edition) based on tumour thrombus level, differentiating the T stage of tumours limited to renal-vein-only involvement. - Objective - We aimed to evaluate the impact of tumour thrombus extension in a multi-institutional cohort of patients. - Design, setting, and participants - An international consortium of 11 institutions was established to retrospectively review a combined cohort of 1215 patients undergoing radical nephrectomy and tumour thrombectomy for RCC, including 585 patients with inferior vena cava (IVC) involvement or higher. - Measurements - Predictive factors of survival, including histology, tumour thrombus level, nodal status, Fuhrman grade, and tumour size, were analysed. - Results and limitations - A total of 1122 patients with complete data were reviewed. The median follow-up for all patients was 24.7 mo, with a median survival of 33.8 mo. The 5-yr survival was 43.2% (renal vein involvement), 37% (IVC below the diaphragm), and 22% with caval involvement above the diaphragm. On multivariate analysis, tumour size (hazard ratio [HR]: 1.64 [range: 1.03-2.59]; p=0.036), Fuhrman grade (HR: 2.26 [range: 1.65-3.1]; p=0.000), nodal metastasis (HR: 1.32 [range: 1.09-1.67]; p=0.005), and tumour thrombus level (HR: 2.10 [range: 1.53-3.0]; p=0.00) correlated independently with survival. - Conclusions - Based on analysis of the largest known cohort of patients with RCC along with IVC and atrial thrombus involvement, tumour thrombus level is an independent predictor of survival. Our findings support the changes to the latest AJCC/UICC staging system.